2021
DOI: 10.51910/ijhdr.v13i46.683
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy in parasitic diseases

Abstract: Background: The use of homeopathic medicines has increased, partly because conventional drugs do not always elicit the desired effects, and partly because their side effects might compromise the patient’s’ adherence to treatment. Several studies showed benefits in the use of highly diluted medicines for the treatment of infectious diseases. Aim: The aim of the present review was to perform a critical discussion about aspects of homeopathy and the current status of veterinary experimentation, as well as of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…27 28 Studies that attest the effectiveness of homeopathic treatment applied to parasitic diseases are still scarce in the scientific literature. 29 Sulphur is a prominent polycrest of the homeopathic Materia Medica 30 and generally has a great affinity with skin pathologies, especially those whose nature is scorching and fetid. The physical pathogenesis of Sulph presents several of the symptoms characteristic of myiasis by C. hominivorax , such as irritating action on the mucous membranes, ulcerative wounds, and generating physical weakness, apathy and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…27 28 Studies that attest the effectiveness of homeopathic treatment applied to parasitic diseases are still scarce in the scientific literature. 29 Sulphur is a prominent polycrest of the homeopathic Materia Medica 30 and generally has a great affinity with skin pathologies, especially those whose nature is scorching and fetid. The physical pathogenesis of Sulph presents several of the symptoms characteristic of myiasis by C. hominivorax , such as irritating action on the mucous membranes, ulcerative wounds, and generating physical weakness, apathy and weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, more applied research is necessary, especially in the context of parasites of veterinary interest. 13 Pyrogenium is considered a homeopathic dynamic antiseptic. 14 The use of Pyrogenium is recommended in treatment of septic fevers, especially puerperal fevers.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, more applied research is necessary, especially in the context of parasites of veterinary interest. 13…”
Section: Introductionmentioning
confidence: 99%
“…15 Homeopathic medicines may improve not only the clinical condition of chronically ill patients, but also treat acute manifestations and infectious diseases. 16,17 Recent studies have reported the antimicrobial activity of homeopathic medicines, even when the law of similarity is not considered. 18,19 Natural compounds and conventional antimicrobial drugs can act synergistically and improve the therapeutic efficiency of the treatment.…”
Section: Introductionmentioning
confidence: 99%